A Design and Fabrication of Fish Feed Pelleting Machine. (International Journal of Scientific Research and Management (IJSRM), 2018)
Abstract. Irrespective of the increasing effort of fish farmers to grow fish continuously and feed the nation with diet full of fish, survey has pointed fish feed as one of the outstanding factors limiting the progress of the farmers as the high cost of the feeds scares poor farmer from active farming. This paper present to you a well-designed and locally fabricated electrically powered fish feed pelleting machine, driven by three electric gear motors of 3hp, 1.8hp and 0.7hp that drive the screw conveyor at the barrel, the hopper conveyor and the extrusion cutter respectively. The components of the machine were locally sourced and locally fabricated. The hopper, the screw conveyors, the barrel and the cutter are made of stainless steel to reduce contamination due to rust. The machine measures 183mm length, 38mm width and 115mm high. It is calculated to have pelleting efficiency of 0.97% and is capable of producing 0.0539kg of feed per second. Keywords: feed, pelleting, fish and machine